The P-mJOA: A Patient-derived, Self-reported Outcome Instrument for Evaluating Cervical Myelopathy. Issue 2 (March 2018) - Rhee, John M.; Shi, Weilong J.; Cyriac, Mathew; Kim, Jin Y.; Zhou, Feifei; Easley, Kirk A.; Patel, Anuj
Abstract : Study Design: Prospective Cohort Study. Objective: The objective of this study is to evaluate and validate a patient-derived version of the modified Japanese Orthopaedic Association (the "P-mJOA") that a patient can complete along with other patient-derived outcome measures. Summary of Background Data: The modified Japanese Orthopaedic Association (mJOA) is a validated instrument widely used in the assessment of cervical myelopathy; however, it is not a patient-derived outcome. If available and reliable, a patient-derived version of the mJOA (P-mJOA) could facilitate research because the data would be immediately available upon patient completion and also remove any potential physician bias. Currently, there is no patient-derived myelopathy survey with the widespread acceptance of the mJOA. Methods: The P-mJOA was created by very slightly modifying the verbiage of the mJOA to make it possible for a patient to complete the instrument while maintaining the questionnaire's core structure. A total of 100 consecutive consenting patients with cervical myelopathy were enrolled. After the patient completed the P-mJOA, the mJOA was scored by a physician blinded to the P-mJOA result. Results: The P-mJOA and the mJOA had identical mean scores of 14.7 (mean difference±SD: 0.0±1.5; P =0.89). Several measures of reliability demonstrated agreement between the 2 surveys, including strong agreement with the intraclass correlation coefficient and Spearman ρ (both 0.83) and moderate to substantial agreement with weighted κ values (0.55 to 0.66). In addition, 67% of patients preferred to fill out the P-mJOA themselves, suggesting low patient burden. Conclusions: The P-mJOA provided identical mean scores to the mJOA in assessing myelopathy with moderate to strong agreement. Comprised of the same 4 questions as the mJOA but slightly reworded for patient comprehension, the P-mJOA also demonstrated low patient burden in completing the survey. We believe the P-mJOA is a promising tool in cervical myelopathy research with the benefits of a patient-derived outcome measure and low patient burden. Level of Evidence: Level II.